Ovarian Tumors in Children and Adolescents: A 10-Yr Histopathologic Review in Korle-Bu Teaching Hospital, Ghana. (July 2016) - Akakpo, Patrick K.; Derkyi-Kwarteng, Leonard; Quayson, Solomon E.; Gyasi, Richard K.; Anim, Jehoram T.
Abstract : To determine the histopathologic types, frequency of occurrence, age distribution, presenting signs, and symptoms of ovarian tumors in children and adolescents diagnosed at the Korle-Bu Teaching Hospital all histopathology slides and request cards of ovarian tumors diagnosed in subjects aged, 0 to 19 yr over a 10-yr period (2001–2010) were reviewed. Biographical and clinical data of the patients were collected. The results were entered into Epi-info to determine the frequency of various ovarian tumors in different age groups and their association with presenting signs and symptoms. A total of 67 (9.5%) ovarian tumors were diagnosed in patients aged 0 to 19 yr of a total of 706 diagnosed in all age groups during the period. The majority [44 (65.7%)] were germ cell tumors, the commonest being mature cystic teratoma. Burkitt lymphoma was the single most common malignant tumor, comprising 6(9%) of all the tumors, although as a group malignant germ cell tumors were still the most common malignant ovarian tumors in children and adolescents. Although germ cell tumors were the most common tumors in this age group (both benign and malignant), Burkitt lymphoma, a peculiar malignant tumor in this subregion, was the single most common malignant tumor of the ovary.